Delayed goodwill impairment charges: An examination of the declined market capitalization - Abdul Majid, Jamaliah; Lode, Nor Asma (Canadian Center of Science and Education, 2015)
This study has two main objectives.First, it examines the extent to which the declined in the market capitalization below the book values of the net assets represents an appropriate proxy for an indication that goodwill may be impaired by listed companies in Malaysia, as an example of listed companies in an emerging market.Using the findings from the first research objective, this study explores cases of late reporting of goodwill impairment losses. Results show that as a stand-alone, the declined in the market capitalization is not an ideal proxy for an indication that goodwill may be impaired, as it does not fully reflect the condition of the cash-generating-units containing goodwill, disclosed in the Notes to the financial statement.However, when the declined in the market capitalization is examined in relation to financial performance of companies and their segment results, it becomes a useful starting point in identifying cases of late reporting of goodwill impairment losses.The study provides important implications for policy makers and relevant authorities, in that, to enhance the quality of financial reporting, the relevant authorities need to closely monitor the disclosure of goodwill impairment by listed companies in the emerging market of Malaysia.